Fabrication and characterization of poly(lactic acid)/poly(épsilon-caprolactone) blend electrospun fibers loaded with amoxicillin for tunable delivering - Malagon Aviles, O. (2014)
Blends of poly(lactic acid) (PLA) and poly(épsilon-caprolactone) (PCL), loaded with different amounts of Amoxicillin antibiotic (AMOX) were electrospun to investigate their release properties and obtain a controlled and tuneable release. The processing parameters for electrospinning were set up and reliable membranes were obtained. Morphology and thermal behaviour were found dependent on the component ratio as well as on the incorporated drug amount. A very different release kinetics of the two pristine polymers, very rapid for PCL and very slow for PLA, reflected in intermediate release time. However comparing the release amount with that predicted by the mixture rule a preferential incorporation of AMOX into PLA can be inferred.